Treatment patterns and costs among patients with OAB treated with combination oral therapy, sacral nerve stimulation, percutaneous tibial nerve stimulation, or onabotulinumtoxinA in the United States. Issue 8 (22nd August 2020) - Kraus, Stephen R.; Shiozawa, Aki; Szabo, Shelagh M.; Qian, Christina; Rogula, Basia; Hairston, John
Abstract: Introduction: Treatment patterns and costs were characterized among patients with overactive bladder (OAB) receiving later‐line target therapies (combination mirabegron/antimuscarinic, sacral nerve stimulation [SNS], percutaneous tibial nerve stimulation [PTNS], or onabotulinumtoxinA). Methods: In a retrospective cohort study using 2013 to 2017 MarketScan databases, two partially overlapping cohorts of adults with OAB ("IPT cohort": patients with incident OAB pharmacotherapy use; "ITT cohort, " incident target therapy) with continuous enrollment were identified; first use was index. Demographic characteristics, treatment patterns and costs over the 24‐month follow‐up period were summarized. Crude mean (standard deviation [SD]) OAB‐specific (assessed by OAB diagnostic code or pharmaceutical dispensation record) costs were estimated according to target therapy. Results: The IPT cohort comprised 54 066 individuals (mean [SD] age 58.5 [15.0] years; 76% female), the ITT cohort, 1662 individuals (mean [SD] age 62.8 [14.9] years; 83% female). Seventeen percent of the IPT cohort were treated with subsequent line(s) of therapy after index therapy; among those, 73% received antimuscarinics, 23% mirabegron, and 1.4% a target therapy. For the ITT cohort, 32% were initially treated with SNS, 27% with onabotulinumtoxinA, 26% with combination mirabegron/antimuscarinic, and 15% with PTNS. Subsequently, one‐third of this cohort received additional therapies. Mean (SD) costs were lowest among patients receiving index therapy PTNS (6959 [7533]) and highest for SNS (29 702 [26 802]). Conclusions: Costs for SNS over 24 months are substantially higher than other treatments. A treatment patterns analysis indicates that oral therapies predominate; first‐line combination therapy is common in the ITT cohort and uptake of oral therapy after procedural options is substantial.